Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/joc.5035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of simulations with the regional climate model REMO over Central Africa and the effect of increased spatial resolution

Abstract: Simulations of the regional climate model REMO at 25 and 50 km (0.44° and 0.22°, respectively) grid spacing are evaluated over Central Africa for the period 1998–2010. The model's ability to simulate various aspects of the observed climate is assessed with a main focus on precipitation characteristics. The results show that the REMO model has a good skill to reproduce the main regional features of the mean climate fields as well as seasonal and annual cycles, although some biases still exist. The model capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
(87 reference statements)
2
24
0
Order By: Relevance
“…The annual overestimation of rainfall in ERAINT over the above countries, coupled with the improvement of ERAINT by RCMs is also observed at the seasonal scale (see supporting information, Figures S1–S8). These features, which are generally induced by topography, are also associated to pressure gradient between CA land and the Atlantic Ocean surface (Vondou & Haensler, ; Vondou et al, ). Thus, the wet biases found here highlight the challenge for ERA‐Interim reanalysis to adequately simulate low‐level clouds and precipitation in CA as recently shown by Dommo et al ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The annual overestimation of rainfall in ERAINT over the above countries, coupled with the improvement of ERAINT by RCMs is also observed at the seasonal scale (see supporting information, Figures S1–S8). These features, which are generally induced by topography, are also associated to pressure gradient between CA land and the Atlantic Ocean surface (Vondou & Haensler, ; Vondou et al, ). Thus, the wet biases found here highlight the challenge for ERA‐Interim reanalysis to adequately simulate low‐level clouds and precipitation in CA as recently shown by Dommo et al ().…”
Section: Resultsmentioning
confidence: 99%
“…In MPI‐REMO, the first phase is strongly overestimated and the second phase is underestimated. This can be related to a misrepresentation of precipitation over the coastal region (Moufouma‐Okia & Jones, ; Vondou & Haensler, ). The spatial correlation values ( r) between each data sets and the observations ensemble mean is also presented on Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this analysis shows that CCLM succeeds to reasonably capture the precipitation climatology as well as the patterns of the associated low‐level circulation over CA, though some deficiencies are still evident. Moreover, biases in precipitation obtained here are generally a problem common to RCMs, but are consistent to those found in other studies with either CCLM (Panitz et al ., ; Dosio et al ., ; Dieng et al ., ) or different RCMs (e.g., Tchotchou and Kamga, ; Gbobaniyi et al ., ; Diallo et al ., ; Mbienda et al ., ; Fotso‐Nguemo et al ., ; Vondou and Haensler, ; Tamoffo et al ., ). Majority of these studies suggested that these biases are mostly linked to the models failure to resolve convective processes and topography than to errors inherited from the lateral boundary conditions.…”
Section: Resultsmentioning
confidence: 99%
“…() with CCLM over the whole African domain, also those of Crétat et al . () and Vondou and Haensler () with WRF and REMO, respectively, over their different regions of interest. In addition, they mentioned that CCLM fails to fully transport the atmospheric moisture from the ocean to the inland regions, in particular over the Guinean Gulf.…”
Section: Introductionmentioning
confidence: 97%